Cash holding or Net Debt, What is Relevant for Indonesian Firms? - Joshi, Himanshu (The South East Asian Journal of Management, 2019)
Paper investigates the firm level determinants of cash holdings by Indonesian firms. It also examines net debt as substitute measure for cash holding in firm’s financial policies. Sample comprises of 483 Indonesian companies listed on Indonesia stock exchange. Study finds that firms with robust cash flows, and higher cost of capital hold more cash. Firms holding greater noncash liquid assets have moderate cash holdings. Cash holding is most relevant for financially constrained firms, and growth firms. Net debt appears to be most relevant element for low growth firms. No hedging firms are indifferent about their cash holdings and net debt.